IDENTIFIKASI PENERAPAN SHP (Standard Hygiene Personil) PADA VESTIBULLE SPS (Short Packaging System) UNIT II DI PT. TIRTA INVESTAMA (AQUA DANONE) KLATEN, JAWA TENGAH - , RIDHA RIZKI NOVANDA; , Dr. Muhammad Affan Fajar Falah, STP,M.Agr ([Yogyakarta] : Universitas Gadjah Mada, 2014)
SHPis a management in performing hygiene for operator entering filler room. Fillingprocess of AQUA cup 240 ml requires higherhygienesince there is no sterilization anymore so that the product can be consumed safely. SHPlocates in vestibule(isolation room beforefiller) and must be well â guarded. Therefore, it is necessary to performed identification of SHP misfit, causing factors of deviation in the most deviation room, and giving positive opinion for vestibulle. The observation was conducted toward operator who did not suit with SHP. It started with observation, data management using normal distribution, categorizing based score, making pieand paretodiagram in accordance with data collecting result. At last, it identified causing factors using ishikawa diagram. Higher improper category happened on bath and shampoo standard as well as drying the body with clean towel. Moderate category was washing hands with the soap and drying process as well as sterilizing the boot into sterbac solution. Meanwhile, low category was changing the clothes and using complete uniform and sterile masker. Further, the most improper room was room of level 4. The improper of room of level 4 was caused by human, material, and environment factor. Hence, the positive suggestion for vestibulleis re-layoutand adding vestibulle, floor and wallre-coatingfacility, standard supporting the display and adding cleaning service.